The Effect of Foot Exercise on Foot Sensitivity in Type II Diabetes Mellitus Patients in Environment IV of Dataran Tinggi Village, Binjai in 2024 - Empraninta, Hanna Ester; Br Bangun, Chusnul Adinta (COVID-19 : Journal of Health, Medical Records and Pharmacy, 2024)
Indonesia is a country with a fairly high incidence rate. Data found that type 2 DM sufferers in Indonesia reached 1.5% or around 4.1 million people from the total population, then one of the complications that arises from diabetes mellitus sufferers is decreased sensitivity in the feet, this phenomenon if left unchecked will become diabetic ulcers. Objective: To determine foot sensitivity before and after implementing diabetes foot exercises. Knowing the differences before and after the implementation of diabetes mellitus foot exercises on foot sensitivity in diabetes mellitus sufferers. This type of research is descriptive research. This implementation was carried out for 7 days with 3 meetings. The respondents used in this study were diabetes mellitus sufferers who experienced decreased sensitivity in their feet, which was characterized by frequent tingling sensations and decreased stimulation. After applying diabetic foot exercises, it showed an increase in foot sensitivity in diabetes mellitus sufferers. Applying diabetic foot exercises can increase foot sensitivity in people with diabetes mellitus.